Jak Hilary został Walą. Przemiana genderowa w przekładach wybranych wierszy dla dzieci na język rosyjski - Manasterska-Wiącek, Edyta (Przegląd Wschodnioeuropejski, 2025)
The aim of this article is a comparative study of five Polish children’s poems and their translations into Russian in which the characters are gender-differentiated in the original and in the translation. The analysis focuses on the consequences of such solutions and their impact on the meaning of the poems and their reading reception. Although the modifications introduced by the translators are not always significant, as shown in one example, in other cases characters constructed in this way are assigned different characteristics in both languages due to their gender, in accordance with gender stereotypes in the culture of the original and the translation. This, in turn, has the effect of changing the meaning of the works under study and their reception.